2018
DOI: 10.1136/bmjqs-2018-008002
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of potentially avoidable emergency admissions in Ireland: an ecological analysis

Abstract: BackgroundMany emergency admissions are deemed to be potentially avoidable in a well-performing health system.ObjectiveTo measure the impact of population and health system factors on county-level variation in potentially avoidable emergency admissions in Ireland over the period 2014–2016.MethodsAdmissions data were used to calculate 2014–2016 age-adjusted emergency admission rates for selected conditions by county of residence. Negative binomial regression was used to identify which a priori factors were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
6
25
0
Order By: Relevance
“…Despite their use to monitor healthcare systems, the effectiveness of ACSCs as an indicator has been debated 15 16. Recent work from Lynch et al 6 concluded that ‘the distinction between potentially avoidable and all other emergency admissions may not be as useful as previously believed when attempting to identify the causes of regional variation in emergency admission rates’, when looking at county-level variation in emergency admissions in Ireland from 2014 to 2016. The researchers found that similar factors (unemployment, hospital admission policy and private health insurance coverage) were associated with both care-sensitive and total emergency admissions.…”
Section: The Multifactorial Nature Of All Hospital Admissionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their use to monitor healthcare systems, the effectiveness of ACSCs as an indicator has been debated 15 16. Recent work from Lynch et al 6 concluded that ‘the distinction between potentially avoidable and all other emergency admissions may not be as useful as previously believed when attempting to identify the causes of regional variation in emergency admission rates’, when looking at county-level variation in emergency admissions in Ireland from 2014 to 2016. The researchers found that similar factors (unemployment, hospital admission policy and private health insurance coverage) were associated with both care-sensitive and total emergency admissions.…”
Section: The Multifactorial Nature Of All Hospital Admissionsmentioning
confidence: 99%
“…They are designed to capture how ambulatory care might impact on rates of emergency admissions. However, in this issue of BMJ Quality and Safety , Lynch et al 6 question the merits of distinguishing ACSCs from other emergency admissions. Examining factors associated with county-level variation in emergency admissions in Ireland, they found similar factors were associated with both all emergency admissions and ACSCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, ACSC analyses to date recognises the impact on emergency departments and admissions. Drivers of these admissions have been examined highlighting the association with levels of primary care provision, as well as higher levels of deprivation 1 8–10. However, the use of ACSC analysis to identify and prioritise areas for improved primary care resources and programmes of care remains unexamined.…”
Section: Introductionmentioning
confidence: 99%
“…Rates of ACSC hospitalisations are also influenced by demographic, socioeconomic and health system factors [21,22]. These factors will in turn influence the case mix of patients, which undoubtedly has an effect on mortality following these admissions.…”
Section: Discussionmentioning
confidence: 99%